2021
DOI: 10.3390/cancers13225737
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Signature Identifying CIN3 Regression and Cervical Cancer Survival

Abstract: The purpose of this study was to establish a gene signature that may predict CIN3 regression and that may aid in selecting patients who may safely refrain from conization. Oncomine mRNA data including 398 immune-related genes from 21 lesions with confirmed regression and 28 with persistent CIN3 were compared. L1000 mRNA data from a cervical cancer cohort was available for validation (n = 239). Transcriptomic analyses identified TDO2 (p = 0.004), CCL5 (p < 0.001), CCL3 (p = 0.04), CD38 (p = 0.02), and PRF1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…In the present study, we identified that TDO2 is highly expressed in 20 types of cancer, including BLCA, BRCA, CESC, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, OV, PAAD, PRAD, READ, SKCM, STAD, TGCT, THCA, UCEC, and UCS, which are in line with previous findings [8][9][10][24][25][26][27][28]. However, Wu et al found that TDO2 was overexpressed in HCC, and their overexpression was correlated with tumor progression and poor prognosis [29,30], which contradicts our current results.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we identified that TDO2 is highly expressed in 20 types of cancer, including BLCA, BRCA, CESC, COAD, ESCA, GBM, HNSC, KIRC, LUAD, LUSC, OV, PAAD, PRAD, READ, SKCM, STAD, TGCT, THCA, UCEC, and UCS, which are in line with previous findings [8][9][10][24][25][26][27][28]. However, Wu et al found that TDO2 was overexpressed in HCC, and their overexpression was correlated with tumor progression and poor prognosis [29,30], which contradicts our current results.…”
Section: Discussionsupporting
confidence: 93%
“…The patients were randomly assigned to a training group and a testing group. The gene expression pro les were merged and normalized using the 'sva' package [9] in R (v4.1.0).…”
Section: Datasets and Pre-processingmentioning
confidence: 99%
“…Finally, the expression of phosphoglycerate dehydrogenase rises continuously as CIN progresses to cancer. Phosphoglycerate dehydrogenase is believed to be involved in carcinogenesis and might be used to predict CIN development [ 6 ].…”
Section: Introductionmentioning
confidence: 99%